Microplastics in commercial clams from the intertidal zone of the South Yellow Sea, China - Tang, Ruikai; Zhang, Tao; Song, Kexin; Sun, Yixin; Chen, Yangjun; Huang, Wei; Feng, Zhihua (Frontiers in Marine Science, 2022)
Clams are commercially important species and are a vital component of the offshore ecosystem. In this study, four species of clams were collected from the intertidal zone of the South Yellow Sea to investigate the distribution and self-purification rules of microplastics. The results showed that there were significant differences in the abundance of MPs in clams in different regions, and the pollution at the high-tide zone was the most serious. The MPs were dominated by fiber in shape, black-grey in color and rayon in composition. During depuration, MPs in various tissues of the clam accumulated in the mantle. The removal of the mantle after 72 h of depuration could reduce the amount of microplastics by nearly half. This method can reduce the annual per capita intake of MPs above 5000 items. The potential risks of microplastics to human health and ecosystems require further research.